The effect of deep and slow breathing on pain perception, autonomic activity, and mood processing - an experimental study - Busch, Volker; Magerl, Walter (Pain medicine, 2012)
Objective: Deep and slow breathing (DSB) techniques, as a component of various relaxation techniques, have been reported as complementary approaches